2017
DOI: 10.1093/mnras/stx1125
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution ALMA observation of the 12CO(3–2) and 350 GHz continuum emissions of the debris disc of 49 Ceti

Abstract: We present high resolution ALMA observations of the CO(3-2) and 350 GHz continuum emissions of the debris disc of 49 Ceti, known to be particularly rich in molecular gas in spite of its age. The main new results are: i) both CO and dust discs share a same position angle and a same inclination but the gas disc is more homogeneous, more central and thinner than the dust disc; ii) evidence is obtained for a significant deficit of observed CO(3-2) emission at Doppler velocities differing from the star systemic vel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
(95 reference statements)
1
4
0
Order By: Relevance
“…These models yield CO masses of 10 −3.8 and 10 −3.5 M ⊕ , respectively, more than an order of magnitude smaller than our CO mass (10 −2.15 M ⊕ ). A similar discrepancy applies to the column density derived by Nhung et al (2017) based on 12 CO 3-2. We find that the 12 CO 2-1 and 3-2 emission is strongly optically thick (τ ∼ 120), while Hughes et al (2017) concluded…”
Section: Appendix a Continuum Fluxessupporting
confidence: 58%
“…These models yield CO masses of 10 −3.8 and 10 −3.5 M ⊕ , respectively, more than an order of magnitude smaller than our CO mass (10 −2.15 M ⊕ ). A similar discrepancy applies to the column density derived by Nhung et al (2017) based on 12 CO 3-2. We find that the 12 CO 2-1 and 3-2 emission is strongly optically thick (τ ∼ 120), while Hughes et al (2017) concluded…”
Section: Appendix a Continuum Fluxessupporting
confidence: 58%
“…The 49 Cet debris disc system was subject to several modelling projects, either concentrating on the dust (e.g., Wahhaj et al 2007;Pawellek et al 2014;Choquet et al 2017), the gas (e.g., Roberge et al 2014;Miles et al 2016) or both components (e.g., Roberge et al 2013;Nhung et al 2017;Hughes et al 2017). In this study we focus on the dust component.…”
Section: Modelling Strategymentioning
confidence: 99%
“…In particular one aims at identifying clearly which physico-chemical conditions need to be fulfilled for planets to start forming. We have studied several young stars [21][22][23], in particular a multiple stellar system, GG Tau A, which is presented below. GG Tau A, located at 150 pc in the Taurus molecular cloud [24,25], is considered to be an archetype of a T-Tauri  solar mass protostar multiple system.…”
Section: Young Starsmentioning
confidence: 99%